Optogenetic Neuronal Stimulation Promotes Functional Recovery After Spinal Cord Injury - Deng, Wei-wei; Wu, Guang-yan; Min, Ling-xia; Feng, Zhou; Chen, Hui; Tan, Ming-liang; Sui, Jian-feng; Liu, Hong-liang; Hou, Jing-ming (Frontiers in Neuroscience, 2021)
Although spinal cord injury is the main cause of disability and death worldwide, there is still no definite and effective treatment method for this condition. Our previous clinical trials confirmed that the increased excitability of the motor cortex was significantly related to the functional prognosis of patients with spinal cord injury. However, it remains unclear which cell types in the motor cortex lead to the later functional recovery and the neural mechanism of recovery. Herein, we used optogenetic technology to selectively activate glutamate neurons in the primary motor cortex and study whether activation of glutamate neurons in the primary motor cortex can promote functional recovery after spinal cord injury in rats and the preliminary neural mechanisms involved. Our results showed that the activation of glutamate neurons in the motor cortex can significantly improve the motor function score in rats and can effectively shorten the incubation period of motor evoked potentials and increase the amplitude of motor potentials. In addition, HE staining and nerve fiber staining at the injured site showed that accurate activation of the primary motor cortex could effectively promote tissue recovery and neurofilament growth (GAP-43, NF) at the injured site of the spinal cord, while the content of some growth-related proteins (BDNF, NGF) at the injured site increased. These results suggested that selective activation of glutamate neurons in the primary motor cortex can promote functional recovery after spinal cord injury and may be of great significance for understanding the neural cell mechanism underlying functional recovery induced by motor cortex stimulation.